ENHANCING THE PROFILE OF PANCASILA STUDENTS AS AN EFFECTIVE STRATEGY IN SHAPING THE CHARACTER OF YOUNG CITIZENS: A LITERATURE REVIEW - Moh. Imron Rosidi (Adisam Publisher, 2025)
This study aims to explore the role of the Pancasila Student Profile in shaping the character of young citizens and to identify effective implementation strategies based on a literature review. In the face of globalisation and rapid social change, character education through the Pancasila Student Profile is an important instrument in maintaining national identity while equipping the younger generation with moral, social, and intellectual values. The research method used is a qualitative literature study, analysing various academic sources, government policies, and relevant research reports. The results of the study show that the six dimensions of the Pancasila Student Profile, namely being faithful and noble, globally diverse, cooperative, independent, critically reasoning, and creative, are a strong foundation for character building. Effective implementation strategies include curriculum integration, project-based learning, strengthening school culture, increasing teacher capacity, and collaboration with families and communities supported by technology and sustainable policies. This study provides recommendations for education stakeholders to strengthen the role of the Pancasila Student Profile in creating a young Indonesian generation that is intelligent, has good character, and is ready to face the challenges of the times.